(untitled) (Nordic Journal of African Studies, 2011)
Violence, insecurity, and severe hunger resulting from the civil war caused hundreds of thousands of Somalis to flee from the country. Now a large number of Somalis, over one million, live in the diaspora. These diaspora communities retain close ties with the homeland and engage in a wide variety of transnational activities. Some of them prefer to return to Somalia. With regard to Somali politics, there are three main areas that diaspora returnees are involved in. Some invest in the private and social sector; others engage in the civil services; while yet others directly compete for higher political positions. This paper will focus on the participation of returned professional politicians in post-war political leadership in the Somali Republic. This research intends to fill the knowledge gap on the political role of the Somali diaspora and, therefore, to contribute to the ongoing wider debate on diaspora and their impact on their homelands. Based on the assumption that Somali diaspora is increasingly dominating the political leadership of the homeland, this paper intends to answer two questions. Firstly, what is the role of the diaspora relative to their local counterparts in the field of political leadership? Secondly, given the leadership skills and experiences accumulated while abroad, particularly in the West, what diaspora political leadership is able to contribute towards peace and a state-building project in post-war Somalia? Raising this second question, my intention –in addition to illustrating the role of political leadership – is also to moderately respond to a perceived weakness in the literature on the diaspora engagement.